Impact of bispectral index monitoring on postoperative delirium in patients undergoing aortic surgery - Santarpino, G (EDIMES Edizioni Internazionali Srl, 2011)
BACKGROUND: Bispectral index monitoring can facilitate anesthesia care. We evaluated the association of Bispectral index with postoperative neurological outcome and delirium in patients undergoing aortic surgery. METHODS: From 2006 to 2009, 292 consecutive patients undergoing aortic surgery were retrospectively reviewed. Patients were classified into 5 groups according to Bispectral index reduction: Group I (≤15%), Group II (15-20%), Group III (20-25%), Group IV (25-30%), and Group V (>30%). RESULTS: The number of patients in each group was : 52 (17.8%), Group I; 125 (42.8%), Group II;68 (23.3%), Group III; 33 (11.3%), Group IV; 14 (4.8%), Group V. The incidence of delirium and neurological events was higher in Group IV and Group V(90.9% and 18.2% in Group IV, and 71% and 79% in Group V; both p<0.001). Only Group V showed a longer intensive care unit stay compared to Group I (13.5±10.3 vs 5.4±6.6 days; p=0.002), Group II (7.3±8.6 days, p=0.005) and Group III (6.7±6.5 days, p=0.015). Group V also showed a longer intubation time compared to Group I (228±211 vs 73±112 hours; p=0.008) and Group II (105±177 hours, p=0.002). CONCLUSIONS: Our data suggest a higher incidence of neurological deficits in patients with a Bispectral index reduction of >25% from baseline. Explanations for these findings are speculative with regard to the underlying mechanisms, and larger studies are warranted to clarify these issues.